Toward an Understanding of Public Health Entrepreneurship and Intrapreneurship - Chahine, Teresa (Frontiers in Public Health, 2021)
Public health entrepreneurship is an emerging field, driven by the desire of public health students and practitioners to be more action oriented. Despite the increasing demand, no framework has been published for teaching public health entrepreneurship. This paper describes a framework used to understand public health entrepreneurship and intrapreneurship for the purpose of pedagogy and practice. To ground this framework in the academic literature, a scoping review of the literature was conducted with application of a snowball method to identify further articles from the bibliographies of the search results. Recurring themes were identified to characterize common patterns of public health entrepreneurship and intrapreneurship. These themes were design thinking, resource mobilization, financial viability, cross-disciplinary collaboration, and systems strengthening. Case examples are provided to illustrate key themes in both intrapreneurship and entrepreneurship. This framework is a starting point to further the discourse, teaching, and practice of entrepreneurship and intrapreneurship in public health. More research is needed to understand implications for power and privilege, capacity building, financing, scaling, and policy making related to entrepreneurship and intrapreneurship in public health.